HIV risk perception and changes in sexual behavior and sexual satisfaction following male circumcision among circumcised males and their female partners from a traditionally noncircumcising community in Kenya, 2012-2014 - Barbara Burmen; Kennedy Mutai; George Otieno Olilo (Journal of Health and Social Sciences)
Introduction: The aim of this study was to determine HIV risk perception, sexual satisfaction and condom use among recently-circumcised sexually-active males and their female partners from a traditionally noncircumcising Kenyan community. Methods: A longitudinal bio-behavioural survey using interviewer-administered structured questionnaires was conducted in Siaya County of Kenya between November 2012 and February 2014 among persons of both genders aged ≥13 years. Male respondents were characterized as ‘recently circumcised’ if they had been circumcised within the 2 years of the interview, ‘previously circumcised’ if prior to this and as ‘uncircumcised’. Sexual satisfaction was measured on a 3-point likert scale (‘satisfied’, ‘no opinion’, ‘dissatisfied’). Logistic regression analysis was carried out to compare self-reported characteristics of the survey respondents by their own (males) or their partners (females) circumcision status. Results: Of 3,285 men interviewed, 1,001 (30%) were circumcised, of whom 247 (25%) were recently circumcised. Of 4,171 women interviewed, 976 (24%) had primary partners who were circumcised of whom 151 (15%) had ‘recently circumcised’ primary partners. Recently circumcised males were more likely to be younger, single and unemployed; similarly, their female partners were more likely to be younger, single and have attained above primary education (P < 0.05). Most of (≥ 90%) all men and women believed that circumcised men are less likely to get HIV infection and felt that both reducing the number of sex partners, and condom use with a partner with unknown HIV status were still necessary despite male circumcision (MC) being available in their community. Majority of males and females (> 90%) were pleased with their own or their partners recent circumcision, sexual performance and condom use. Discussion and Conclusion: Messages to promote MC should incorporate information regarding preserved/enhanced sexual satisfaction, ease of condom use, and include women to promote MC, a onetime intervention, which is not associated with risk compensation.